Pegylated interferon in HBeAg-positive and -negative chronic hepatitis B patients: post-treatment 1-year results of three Turkish centres. (December 2014) - Yamazhan, Tansu; Kurtaran, Behice; Pullukçu, Hüsnü; Yüksel, Esma; Özkaya, Deniz; Taşbakan, Meltem Işıkgöz; Sipahi, Oğuz Reşat; Durusoy, Raika; Aksu, Hasan Salih Zeki
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, we aimed to evaluate the 1-year post-treatment follow-up results of 112 patients who received pegylated interferon (PEG-IFN) for 52 weeks. HBeAg negativity/seroconversion and/or negative HBV-DNA at the end of the treatment were considered as response. Patients who had response at the end of treatment but had HBV-DNA breakthrough during 1-year follow-up were considered as relapse. The study group comprised 112 cases (34 HBeAg-positive, 78 HBeAg-negative). In HBeAg-positive and -negative cases, end-of-treatment response rates were 2·9% and 60·2%, whereas 1-year sustained virological response rates were 0 and 33·3%, respectively. When we compared relapse cases versus cases with response at the end of 1-year follow-up, being female and having low viral load were the two parameters associated with higher response rates (Chi-square, P = 0·028; Mann–Whitney U test, P = 0·023). Overall non-response rates to PEG-IFN were high (57·1%). Results in HBeAg-positive cases were disappointing.